Impact of γ-irradiation on dielectric and electric properties of TlInS₂ crystals - Sardarly, R.M.; Samedov, O.A.; Salmanov, F.T.; Aliyeva, N.A. (Вопросы атомной науки и техники, 2019)
The effect of γ-irradiation on the relaxor properties of the TlInS₂ compound have been studied. It is established that in this compound the Vogel-Fulcher temperature (Tf) shifts towards the low temperatures, and the Burns temperature (Td) moves towards the high temperatures. As a result, the temperature range for the existence of a relaxor state extends by ∼ 40 K. The presence of hopping conduction is established and the parameters characterizing this mechanism are determined.